Never Been: An Exploration of the Influence of Dis/ability, Giftedness, and Incarceration on Adolescents in Adult Correctional Facilities - Jones, Kelsey Marie (2015)
This dissertation study explores the experiences of incarcerated youth, specifically the relationships between dis/ability (Baglieri& Knopf, 2004), giftedness, and incarceration in the lives of these young people. The extant literature rarely addresses these relationships through the voices of young people who have experienced incarceration first-hand; furthermore, the research pathologizes incarcerated youth and removes the challenges they encounter from their systemically oppressive contexts. This research places the unique experiences of the participants in the larger conversations of deficit-thinking, racism, ecological systems and theories of critical praxisâ??specifically, through the lenses of Dis/ability Studies in Education and Critical Race Theory. As a qualitative research study, this dissertation includes the stories and experiences of three formerly-incarcerated individuals who were held in adult correctional facilities as adolescents, as well as a non-profit leader who is deeply involved in prison abolition and movements that work to improve the lives of inmates. The focus on qualitative methodology and methods works to broaden conversations on juvenile justice and include perspectives on competence, youthâ??s strengths, and resistance to deficit-oriented research. This dissertation argues that we must challenge deficit-oriented models to develop the best pedagogical practices for exceptional students and useful methods for disrupting oppressive systems within educational spaces. Through the centering of participant voices, this study provides implications for understanding dis/ability and the giftedness of young people in exceptional learning environments, the need for close attention to the final stages of the school-to-prison pipeline, and the development of new theories of understanding